2011
DOI: 10.1111/j.1540-8175.2011.01515.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Performance Index and Atrial Ejection Force in Patients with Duchenne's Muscular Dystrophy

Abstract: MPI might be a useful parameter for early detection of occult cardiac dysfunction in DMD patients when other simple and standard echocardiographic parameters are within the normal limits. Lack of atrial contribution in LV filling due to atrial contractile dysfunction may play a role in DMD cardiac dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…The right ventricle, with its small mass and potentially smaller lesion sizes may be underrepresented in these studies. It is important to note that there remains little difference in hemodynamic function between the right and left ventricles of the mdx mouse; similar results are seen in DMD patients (6,58). The failure to observe interventricular hemodynamic differences may result from the tight coupling of the ventricles, in that dysfunction of the right ventricle will lead to dysfunction of the left ventricle.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The right ventricle, with its small mass and potentially smaller lesion sizes may be underrepresented in these studies. It is important to note that there remains little difference in hemodynamic function between the right and left ventricles of the mdx mouse; similar results are seen in DMD patients (6,58). The failure to observe interventricular hemodynamic differences may result from the tight coupling of the ventricles, in that dysfunction of the right ventricle will lead to dysfunction of the left ventricle.…”
Section: Discussionsupporting
confidence: 66%
“…6). Interest- ingly, a similar shortening of the ejection period has been observed using tissue Doppler echocardiography in DMD patients (58). This shortened pressure transient is also present in younger mdx mice, suggesting that it is not related to the progression of dystrophic cardiac disease.…”
Section: Discussionmentioning
confidence: 63%
“…Shabanian et al also found increased mitral A wave velocities, decreased mitral E wave velocities, and decreased TDI lateral peak E wave velocities in patients with DMD. [22] Furthermore, we observed a good correlation between readers for PWD mitral E wave measures (ICC=0.82), PWD mitral A wave velocities (ICC=0.63) and TDI lateral LV peak E’ velocities (ICC=0.72). These results demonstrate that conventional measures of diastolic function are easy to obtain and can detect early changes in myocardial function during longitudinal studies in young children with DMD.…”
Section: Discussionmentioning
confidence: 61%
“…[33] Previous studies showed that MPI was increased in participants with MD who demonstrated normal cardiac function by systolic measures. [11, 22, 34, 35] We therefore looked at the utility of MPI as an early marker of cardiac dysfunction in our DMD cohort. PWD MPI detected subclinical disease in more subjects than TDI.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of dystrophin causes widespread effects on muscle signaling and metabolic pathways, leading to cell death and progressive replacement of functional muscle fibers with fibrotic connective tissue. This process results in profound muscle weakness, usually leaving DMD boys wheelchair-bound by their early teenage years and leading to death from the consequences of respiratory and/or cardiac muscle failure by age [20][21][22][23][24][25][26][27][28][29][30]. Current treatments, such as corticosteroids, slow disease progression only marginally (1), whereas gene-based approaches, such as exonskipping, although promising in preclinical studies, will need to overcome many technical and regulatory hurdles, as well becoming affordable, before they are a widely available therapy for DMD patients (2).…”
mentioning
confidence: 99%